2009
DOI: 10.1002/qua.22343
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between quantum chemical indices and the pKas of a diverse set of organic phenols

Abstract: ABSTRACT:In earlier studies (Gross and Seybold, Int J Quantum Chem, 2001, 85, 569; Gross et al., Int J Quantum Chem, 2002, 90, 445), it was shown that variations in several calculated quantum chemical charge and energy parameters were strongly correlated with the pK a variations in a set of substituted phenols. Here, we examine whether this approach can be extended to the pK a s of a diverse set of more complex organic phenolic compounds. Three levels of theory were tested: (1) the RM1 semiempirical method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…QM QSPR models for p K a prediction in phenols, similar to those presented in this paper (i.e., employing similar charges) were previously published by Gross and Seybold [22], Kreye and Seybold [23] and Svobodova and Geidl [24]. Table 5 shows a comparison between these models and the models developed in this study.…”
Section: Resultsmentioning
confidence: 73%
“…QM QSPR models for p K a prediction in phenols, similar to those presented in this paper (i.e., employing similar charges) were previously published by Gross and Seybold [22], Kreye and Seybold [23] and Svobodova and Geidl [24]. Table 5 shows a comparison between these models and the models developed in this study.…”
Section: Resultsmentioning
confidence: 73%
“…It is apparent from the ESP maps above and those in Figure 2 that the depiction of an atomic charge in a molecule as a single number, despite the usefulness of such numbers in numerous applications [10,[14][15][16], is clearly limited and fails to represent the complexity of the actual charge distribution. Note the positive regions (blue and green) on the bromine ESP surface and (green) on the chlorine surface.…”
Section: Gross Hadad and Seyboldmentioning
confidence: 93%
“…Nonetheless, the concept of an atomic charge in a molecule has historically been an especially important tool for chemists, and a variety of schemes, both quantum chemical and empirical, have been proposed to represent partial atomic charges [9,10]. Among the quantum chemical schemes, charges based on the natural population analysis (NPA) approach of Reed et al [11] and the atoms in molecules (AIM) approach of Bader [12] have been shown in earlier studies to correlate strongly with variations in a variety of molecular physical and chemical properties, such as inversion barriers and pK a s [13][14][15][16], and these measures of partial atomic charge have therefore been examined in the present work. Also, charges calculated by the empirical method of Gasteiger et al [17][18][19], which is based on Sanderson's principle of electronegativity equalization, were determined.…”
Section: Introductionmentioning
confidence: 99%
“…[84] For the two reactions in Scheme 17, two reactions are given without the corresponding reaction time, because the original publication only reported "monitored by TLC". In very few cases, the collection as precipitates from the reaction mixture was reported, which is the usual method for the isolation of squaraine dyes.…”
Section: Synthesismentioning
confidence: 99%